2019
DOI: 10.31181/dmame1902001v
|View full text |Cite
|
Sign up to set email alerts
|

A fuzzy inference system applied to value of information assessment for oil and gas industry

Abstract: Value of information is a widely accepted methodology for evaluating the need to acquire new data in the oil and gas industry. In the conventional approach to estimating the value of information, the outcomes of a project assessment relate to the decision reached following Boolean logic. However, human thinking logic is more complex and include the ability to process uncertainty. In addition, in value of information assessment, it is often desirable to make decisions based on multiple economic criteria, which,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Then, in such a map, robot paths are planned, at the same time pedestrian trajectories are simulated (on the basis of previous observations), and based on that, new costs are defined in a cost map proportional to the hindrance probability at each cell. The paper [37] presents similar cloud-based path planning concept using D* Lite algorithm, but there the implementation of Multi-criteria decision making (MCDM) using Full consistency method (FUCOM) for improvement the efficiency of path planning is proposed. The application of MCDM using FUCOM provides an adaptive approach to path planning, in terms of optimizing the global cost map taking into account all factors affecting the robots motion in the environment and having in mind a mission specificity that requires the management of risks arising from different sources.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, in such a map, robot paths are planned, at the same time pedestrian trajectories are simulated (on the basis of previous observations), and based on that, new costs are defined in a cost map proportional to the hindrance probability at each cell. The paper [37] presents similar cloud-based path planning concept using D* Lite algorithm, but there the implementation of Multi-criteria decision making (MCDM) using Full consistency method (FUCOM) for improvement the efficiency of path planning is proposed. The application of MCDM using FUCOM provides an adaptive approach to path planning, in terms of optimizing the global cost map taking into account all factors affecting the robots motion in the environment and having in mind a mission specificity that requires the management of risks arising from different sources.…”
Section: Related Workmentioning
confidence: 99%
“…The fuzzy rules for determining the traversal cost of cells in the map are constructed as in Table 1. Fuzzy logic techniques are efficient in solving complex, ill-defined problems that are characterized by uncertainty of environment and fuzziness of information [36,37]. Taking into account that disturbances and noises are common sources of uncertainties, it can be concluded that from the aspect of fuzzy implementation this system is highly resistant to noise and disturbance [38,39,40].…”
Section: Figurementioning
confidence: 99%
“…There are two main groups of the learning techniques which can be used to solve this issue. First of them is the connection of artificial neural networks and fuzzy systems which is widely applied decision-making and data classification problems [37][38][39]. The second one is connection of genetic algorithms and fuzzy logic which is implemented in automatic fuzzy model generation and data classification problems solutions [40,41].…”
Section: The Performed Industrial Researchmentioning
confidence: 99%
“…T-S fuzzy systems proposed by Takagi and Sugeno in 1985 are an effective tool for approximation of uncertain nonlinear systems based on fuzzy if-then implication rules, and each rule refers to a local linear system, so the T-S fuzzy model approximates the original nonlinear system [ 10 , 11 ]. T-S model is very powerful tool which is implemented in many prediction or assessment fields, like transport [ 12 ], energy [ 13 ], chemical industry [ 14 , 15 ], aerospace [ 16 ] etc.…”
Section: Introductionmentioning
confidence: 99%